Revisiting Culture and Meaning-Making in World-Systems Analysis: A Proposal for Engaging with the Cultural Political Economy Approach. (July 2020) - Mueller, Jason C.; Schmidt, Steven
World-systems analysis (WSA) understands socio-cultural phenomena as fundamental to the operation of global capitalism, whether through geocultures that sustain centrist liberalism, the emergence of capitalist subjectivities, or by generating structures of knowledge that bound political possibilities. Nonetheless, many scholars critique WSA's treatment of culture as reductive and epiphenomenal. How can we theorize culture's relationship to global capitalism without assuming that culture merely "dupes" participants into reproducing exploitative structures? In this article, we offer a critical evaluation of WSA's treatment of culture and argue that its alleged failings can be ameliorated by adopting a cultural political economy (CPE) framework, an analytical approach that has developed separately from WSA. To do so, we outline WSA's major theorizations of culture; namely, its discussion of global geocultures and structures of knowledge. Departing from existing critiques of WSA, we discuss the applicability of CPE, which examines how discourses both influence and are shaped by the material world. Using anti-systemic movements, populism, and race-making in the world-system as examples, we demonstrate how a CPE-oriented approach permits WSA to address its major cultural critiques. Broadly, we call for a theoretical co-mixing of CPE and WSA, allowing researchers to address the alleged cultural failings of world-systems scholarship.